The Effect of Leader-Member Exchange on Organizational Commitment - Yip, Foon Yee; Khishar Muhammad, Mohd Faizal Segaran (INTI International University, 2019)
With the recent increase in number of education industry in Malaysia as well as the Ministry of Higher Education project to increase it even more in the future, education industries are facing problem to retain employee and maintain the organizational commitment of their employee. The purpose of present study is to examine the influence of leader-member exchange (LMX) on the organizational commitment of education industry in Nilai, Malaysia. A total of 400 questionnaires were distributed but only 232 questionnaire were found to be usable for this study. The present study were analysed by using Smart PLS. It was found that affect, loyalty, contribution, narcissism and ethnocentrism are significantly effect on organizational commitment. It can be concluded that leader exchange member play important role in organizational commitment especially in education industry. Limitations of present study are discussed. Implications of the findings and areas for future research are also presented.